Multiple Criteria Decision Analysis: State of the Art Surveys - Greco, Salvatore; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2005)
MULTIPLE CRITERIA DECISION ANALYSIS: State of the Art Surveys is the most comprehensive work available to survey the state of the art in MCDA to date. Its 24 chapters are organized in eight parts and are written by 49 international leading experts. Each of these parts covers one of the central streams of multiple criteria decision analysis literature. These literature streams are: MCDA today, Foundations of MCDA, Outranking Methods, Multiattribute Utility Theory, Non-Classical MCDA Approaches, Multiobjective Mathematical Programming, Applications, and MCDM Software. The handbook presents the most up-to-date discussions on well-established methodologies and theories in the field, while systematically surveying emerging fields in MCDA such as conjoint measurement, fuzzy preferences, fuzzy integrals, rough sets, etc. MULTIPLE CRITERIA DECISION ANALYSIS is a valuable reference volume (more than 2000 references) for the field of decision analysis. It provides graduate students, researchers, and practitioners with a sweeping survey of MCDA theory, methodologies, and applications. It is a handbook that is particularly suitable for use in seminars in Decision Analysis, Decision Support, and Decision Theory.
Paradigms and Challenges -- Preference Modelling -- Conjoint Measurement Tools for MCDM -- Electre Methods -- Promethee Methods -- Other Outranking Approaches -- Maut — Multiattribute Utility Theory -- UTA Methods -- The Analytic Hierarchy and Analytic Network Processes for the Measurement of Intangible Criteria and for Decision-Making -- On the Mathematical Foundation of MACBETH -- Dealing with Uncertainties in MCDA -- Choice, Ranking and Sorting in Fuzzy Multiple Criteria Decision Aid -- Decision Rule Approach -- Fuzzy Measures and Integrals in MCDA -- Verbal Decision Analysis -- Interactive Methods -- Mutiobjective Programming -- Multiple Objective Linear Programming with Fuzzy Coefficients -- MCDM Location Problems -- Multicriteria Decision Aid/Analysis in Finance -- MCDA and Energy Planning -- Multicriteria Analysis in Telecommunication Network Planning and Design — Problems and Issues -- Multiple Criteria Decision Analysis and Sustainable Development -- Multiple Criteria Decision Support Software.
Keywords: elektronické knihy; electronic books; Operations research; Management science; Econometrics; Mathematical optimization; Mathematical models; Production management; Operations Research and Decision Theory; Operations Research, Management Science; Econometrics; Optimization; Mathematical Modeling and Industrial Mathematics; Operations Management